Platelet lymphocyte ratio (PLR), neutrophil lymphocyte ratio (NLR), and diastolic dysfunction as neonatal sepsis mortality predictors in preterm neonates - Tampy, Safitri Tia; Hidayah, Dwi; Lilijanti, Sri (Indonesian Pediatric Society, 2025)
Background Neonatal sepsis is a significant challenge in neonatal care, particularly among preterm neonates who are highly vulnerable due to their underdeveloped immune systems. Traditional markers for predicting the outcomes of neonatal sepsis, such as procalcitonin and C-reactive protein, are not always available all across places. Objective To evaluate the predictive value of platelet lymphocyte ratio (PLR), neutrophil lymphocyte ratio (NLR), and diastolic dysfunction for neonatal sepsis mortality in preterm neonates. Methods A prospective cohort study was conducted in 42 preterm neonates with neonatal sepsis admitted to Dr. Moewardi Hospital. The PLR and NLR were collected at two time points: the first blood specimen was drawn within the first 24 hours of life and the second was collected 72 hours later. Diastolic function was assessed by echocardiography performed within 48–72 hours after the diagnosis of sepsis. Mortality during treatment was recorded as the dependent variable. The relationships among these variables were analyzed with bivariate and multivariate analyses, and the significance level was set at P<0.05. Results Of 42 subjects, 57.1% died. Increased NLR and diastolic dysfunction were significantly associated with an increased risk of mortality (OR=3.64; P=0.049 and OR=25.0; P<0.001, respectively), while PLR was not. Multivariate analysis revealed that diastolic dysfunction remain a significant independent predictor of mortality (adjusted OR=28.9;P=0.001), whereas NLR did not maintain statistical significance (P=0.093). Conclusion Diastolic dysfunction was an independent predictor of mortality in preterm neonatal sepsis. The NLR and PLR did not associate with mortality in preterm neonatal sepsis. Rigorous monitoring of cardiovascular function is crucial in the management of neonatal sepsis.